The effect of alcohol-based virucidal hand sanitizers on skin barrier function: a randomised experimental study - Gina, Michal; Ofenloch, Robert; Schwebke, Ingeborg; Hübner, Nils-Olaf; Brüning, Thomas; Fartasch, Manigé (Contact dermatitis, 2025)
Background Applying alcohol-based hand rubs (ABHRs) is a proven means of combating hand-borne microorganisms. In addition to their bactericidal activity, some rubs also have virucidal properties (ABVHRs). Frequent use of ABHRs can result in skin irritation. Objectives This study investigates the impact of four commercially available ABVHRs on skin function (ABVHR A-D). ABVHR-A and ABVHR-B contained ethanol in higher concentrations, whereas ABVHR-C and ABVHR-D comprised ethanol and 1-propanol at lower concentrations combined with phosphoric acid (PA). Methods Using occlusion-modified tandem irritation tests and standard bioengineering methods, we assessed the effects of these ABVHRs and controls (ethanol, isopropanol, PA, water) on 48 healthy Caucasian volunteers' skin. Results In general, alcohols and ABVHRs were well tolerated. However, the results revealed significant changes in transepidermal water loss (TEWL), corneometry, and colorimetry between baseline and day 3 for all ABVHRs and controls, particularly for ABVHR-D (TEWL change 6.43 (SD 1.40) to 8.76 (SD 3.87)). Although the differences between the ABVHRs were not statistically significant, ABVHR-A and ABVHR-D significantly increased TEWL compared to water. Most ABVHRs demonstrated a better skin irritation profile than pure ethanol (80%) and isopropanol (70%). PA slightly reduced corneometry values. Conclusions This study suggests that the irritative potential of ABVHRs varies, likely due to differences in alcohol type (1-propanol in particular) and concentration. At the tested concentration, PA appears to be well tolerated and may enhance virucidal activity without significantly increasing skin irritation.
Gesehen am 06.10.2025